Art Education Art Learning in Pandemic For Students Of Elementary School (Case Study Students Of Inpres Elementary School of Sikumana Village in Disctrict 29th Kupang): Art Education - Sogen, Yosephina Katharina (CV. Inara, 2021)
This study is a case study that how music learning and visual art thought during the Pandemic of COVID-19. Students are learning from home who learn the art of music and fine arts by offline learning. Elementary School Pre-Service Teacher conducted experiments to increase student motivation and provide learning experiences during the Pandemic. Art learning, especially the practice of music and fine arts during this 'long holiday', is not given optimally because online learning experiences various advantages. The purpose of this study is to overcome the issue of practical art learning that is carried out at home by conducting Home Visit. These activities are carried out so that the learning of music and fine arts can be understood well by students. The practice of music and fine arts through song and movement and creating collages can provide students with great enthusiasm for learning and provide an important artistic practice experience for learning. The practice of art by directly meeting with students can lead students to study well. Students are given examples in practicing the art of music, song and movement that can directly inspire students to be brave and activate kinesthetic intelegence through movements and provide good motor activities. The art of collage gives students an experience of cutting and placing pieces of plastic material into pictures neatly.